Eficiência agronômica da aplicação foliar de nutrientes na cultura da soja - Coelho, Hugo Alexandre [UNESP]; Grassi Filho, Helio [UNESP]; Barbosa, Rodrigo Domingues [UNESP]; Romeiro, Júlio César Thoaldo [UNESP]; Pompermayer, Guilherme Verdicchio [UNESP]; Lobo, Thomaz Figueiredo [UNESP] (My University, 2011)
The need to increase soybean production has led many producers to seek alternatives, one of them is the use of foliar fertilization. The aim of this study was to evaluate the agronomic effectiveness of different doses of foliar applications of Mg, Zn and B in soybean. The experiment was installed in the area of the Department of Natural Resources/Area of Soil Science, Faculty of Agronomic Sciences, UNESP, Botucatu, São Paulo, Brazil, in an Oxisol. The design was completely randomized design with eight treatments and foliar applications of ten repetitions, for a total of eighty vessels. It was observed that the treatment (17% B +20% Zn) had a higher efficiency in fresh weight, dry weight and height of soybean, as compared to the productive treatment (17% B + 10% Mg) was what gave the best performance among the treatments.

A necessidade de aumentar a produção da soja tem levado o produtor a buscar inúmeras alternativas, uma delas é a utilização da adubação foliar. O objetivo do estudo foi avaliar a eficiência agronômica de diferentes doses de aplicações foliares de Mg, Zn e B na cultura da soja. O experimento foi instalado na área do Departamento de Recursos Naturais/Área de Ciência do Solo, da Faculdade de Ciências Agronômicas – UNESP/Campus de Botucatu, Estado de São Paulo, Brasil, num Latossolo Vermelho Distrófico. O delineamento estatístico foi inteiramente casualizado, com oito tratamentos de aplicações foliares e dez repetições por tratamento, perfazendo um total de oitenta vasos. Observou-se que o tratamento (17% de B +20% de Zn) obteve uma maior eficiência no peso fresco, peso seco e altura da soja, já em relação aos parâmetros produtivos o tratamento (17% de B + 10% de Mg) foi o que obteve o melhor desempenho entre os tratamentos.
Agronomic efficiency of leaf application of nutrients in the soybean crop
Keywords: Leaf fertilizer; Glicine max; Vegetative and productive parameters; Adubação foliar; Glycine max; Parâmetros vegetativos e produtivos